Apuntes fenomenológicos sobre el ser (el ser-en-sí, el ser-para-sí) y su relación con la conciencia en la filosofía de Sartre (2022)
In his first phenomenological writings Jean-Paul Sartre supports the thesis that consciousness is pure exteriority, that is, there is no interiority in consciousness that could harbor metaphysical instances, as could be the self, the cogito, the unconscious, etc. Already for Being and Nothingness, the French philosopher will maintain this thesis, deepening it and establishing a dialogue with his theory of being. To this extent, the article intends to explore such relationship, in order to know the place occupied by the notion of consciousness in Being and Nothingness.